Novel heterocyclic hybrids of pyrazole targeting dihydrofolate reductase: design, biological evaluation and insilico studies. (1st January 2020) - Othman, Ismail M. M.; Gad-Elkareem, Mohamed A. M.; Amr, Abd El-Galil E.; Al-Omar, Mohamed A.; Nossier, Eman S.; Elsayed, Elsayed A.
Abstract: A novel series of pyrazole analogues including hydrazones, pyrazolo[4, 3- c ]-pyridazines, pyrazolo[3, 4- e ][1, 2, 4]triazine and pyrazolo[3, 4- d ][1, 2, 3]triazoles was designed, synthesised and screened for their in vitro antimicrobial and DHFR inhibition activity. Compounds bearing benzenesulphonamide moiety incorporated with 3-methyl-5-oxo-1 H -pyrazol-4(5 H )-ylidene) hydrazine 3a or 6-amino-7-cyano-3-methyl-5 H -pyrazolo[4, 3- c ]pyridazine 6a revealed excellent and broad spectrum antimicrobial activity comparable to ciprofloxacin and amphotericin B as positive antibiotic and antifungal controls, respectively. Furthermore, these derivatives proved to be the most active DHFR inhibitors with IC50 values 0.11 ± 1.05 and 0.09 ± 0.91 µM, in comparison with methotrexate (IC50 = 0.14 ± 1.25 µM). The in silico studies were done to calculate the drug-likeness and toxicity risk parameters of the newly synthesised derivatives. Additionally, the high potency of the pyrazole derivatives bearing sulphonamide against DHFR was confirmed with molecular docking and might be used as an optimum lead for further modification.